Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar Pancasila Peserta Didik Kelas II SD: The Influence of the Problem Based Learning (PBL) Learning Model on Pancasila Learning Outcomes of Grade II Elementary School Students - Helga Putri Fatmawati; Sri Suwartini; Isna Rahmawati (ITScience (Information Technology and Science), 2026)
This research is motivated by the low learning outcomes in Pancasila Education among second-grade elementary school students, who are still predominantly using conventional learning methods and lack student involvement. The Problem-Based Learning (PBL) model is seen as an alternative that can improve understanding through contextual problem-solving. This study aims to determine the effect of the PBL model on learning outcomes of Pancasila Education. The study used a quantitative, quasi-experimental design with a pretest-posttest control group. The study population comprised all second-grade students at Jombor State Elementary School, and a purposive sampling technique was used to select the sample. The research instrument was a validated, reliable learning outcome test. Data were analysed using normality and homogeneity tests, and the t-test for hypothesis testing. The results showed a significant difference between the experimental group using the PBL model and the control group using conventional methods. The average learning outcomes of students in the experimental group were higher than those in the control group. These findings indicate that the application of the Problem-Based Learning model has a positive and significant effect on learning outcomes of Pancasila Education. This research implies that the PBL model can be used as an effective alternative learning strategy to improve the quality of learning in elementary schools, especially in building conceptual understanding and student active involvement.